The Antibacterial Effects of Cocktail and Single Forms of Lytic Phages Belonging to Podoviridae and Myoviridae Families from Sewage against Shigella sonnei and Shigella flexneri. (25th November 2022) - Jokar, Javad; Rahimian, Niloofar; Ghasemian, Abdolmajid; Najafipour, Sohrab
Abstract : Background . Diarrhea caused by bacterial pathogens such as Shigella spp. is one of the prominent public health concerns. The evolution of vast antibiotic resistance by these pathogens, leading to failure in the infections eradication, has made an impetus to seek and develop novel approaches. Recently, some alternative therapies such as phage therapy have been investigated. Bacteriophages are viruses that target specific bacterial species. The objective of this study was to assess the therapeutic effect of phages obtained from hospital sewage against Shigella sonnei ( S. sonnei ) ATCC® 9290 and S. flexneri ATCC 12022 standard and clinical strains. Methods . Four various lytic bacteriophages were isolated from animal fecal and sewage samples and propagated using S. sonnei and S. flexneri as host organisms. The phages' morphology was determined using transmission electron microscopy (TEM). The lytic potential and host specificity of isolated phages were evaluated using double layer plaque assay and spot test. Moreover, bacterial turbidity values were evaluated in coculture with phages in the Luria Bertani (LB) medium for 24 hours at time intervals of 30 min. Results . Phage cocktails (Shs1, Shs2, Shf1, and Shf2) exhibited higher antimicrobial activity than single phage application against S. sonnei and S. flexneri standard strains. The phages belonged to Podoviridae and Myoviridae families according to TEM-assisted morphological features analysis. In addition, the phages exhibited host specificity using the spot test against 18 Shigella clinical isolates. Conclusion . In this study, phage cocktail of Podoviridae and Myoviridae families from sewage conferred substantial antibacterial effects against S. sonnei and S. flexneri . However, single phage effects were unstable in the LB coculture. Moreover, the phages had host specificity using the spot test performed against Shigella spp. clinical isolates.